Technical Oral Presentations (TOP) in EFL engineering education: A systematic literature review on workplace communication preparedness - Younus, Muhammad; Abdullah Adnan, Mohamed; Fatimah, Ali; Mohd Rashid, Ab Hamid (Sciedu Press, 2025)
Workplace communication is a critical skill for engineering graduates, particularly those in English as a Foreign Language (EFL) contexts, where language proficiency can impact career success. This systematic literature review examines the effectiveness of Technical Oral Presentation (TOP) in enhancing workplace communication skills among EFL engineering undergraduates. The review synthesises recent studies (2015-2024) on TOP, focusing on its role in improving technical articulation, fluency, audience engagement, and professional presentation skills. There were a total of studies (n = 60) that were analysed. The analysis indicates that TOP fosters clarity in delivering complex engineering concepts, enhances confidence in spoken English, and develops essential soft skills such as teamwork and adaptability. Additionally, structured feedback and repeated practice contribute to the reduction of language-related psychological factors such as anxiety, lack of self-confidence and fear of making mistakes and speaking in public. However, challenges such as limited exposure to authentic workplace scenarios and language communication barriers persist. The study highlights the need for pedagogical frameworks integrating industry-relevant communication strategies with engineering curricula. This review concludes that while TOP is a valuable tool in preparing EFL engineering students for professional environments, its effectiveness depends on structured implementation, targeted feedback, and alignment with real-world communication demands. Future research should explore innovative approaches, such as digital tools and immersive learning, to further enhance TOP’s impact.